TOXICITY OF METHANOL EXTRACT OF JATROPHA GOSSYPIFOLIA L. (BELLYACHE) TO THE JUVENILES OF CLARIAS GARIEPINUS, (BURCHEL) - I., USMAN J.; M., ABJIT; Y., ABUBAKAR J.; K., DAUDA A.; Y., ALIYU; M., SANI A. (Journal of the Inland Fisheries Society of India, 2021)
Juveniles of Clarias gariepinus (Burchel) of length 15.75 Â± 00.50 cm and weight 14.75 Â± 1.25g were exposed to methanol extract of Jatropha gossypifolia L. at concentrations of 0.00, 3.00, 4.00, 5.00, 6.00 and 7.00 mgl-1 in three replications for 96 hours to determine the acute toxicity. Agitated swimming, loss of balance, ventral resting position, and death were observed as symptoms of toxicosis. Opercular ventilation was significantly higher than the control at P